2001
DOI: 10.1017/s1357729800055879
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and behavioural responses in blue foxes (Alopex lagopus) : comparisons between space quantity and floor material

Abstract: Welfare-related physiological and behavioural responses were studied in farmbred blue foxes (Alopex lagopus). Comparisons in space quantity were made between two different-sized shed cages (50 cm long (W50) and 120 cm long (W120); each 105 cm wide ✕ 70 cm high) and for one out-of-shed pen (5 m long ✕ 3 m wide ✕ 1·8 m high; W500). Each option had a wire-mesh floor. Furthermore, we tested how floor material affects responses by comparing the W500 foxes in wire-mesh floor pens with foxes housed in earthen floor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The higher incidence of hyperaemia found in the block and straw animals is thus another potential explanation for differences in body growth. Impaired growth may also affect skin and body length (Korhonen et al 2001). Skin length was found to be shortest in BL 7 animals, which can be assumed to be a result of the lowest final body weight in this group.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The higher incidence of hyperaemia found in the block and straw animals is thus another potential explanation for differences in body growth. Impaired growth may also affect skin and body length (Korhonen et al 2001). Skin length was found to be shortest in BL 7 animals, which can be assumed to be a result of the lowest final body weight in this group.…”
Section: Discussionmentioning
confidence: 86%
“…If the fox did not start eating within 30 s, it was considered fearful (Rekilä et al 1997;Korhonen et al 2001). Before the test, feed was withheld from the animals for 24 h.…”
Section: Behavioural Testsmentioning
confidence: 99%
“…The corresponding phenotypic correlations were negative, indicating that large size, fatness and fast growth rate to some extent impair the fox's ability to move about in the cage. In a study by Korhonen et al (2001), foxes on an earthen floor enclosure received higher scores for LEG than foxes in traditional wire-mesh cages. The authors concluded that the higher MOVE in pen conditions had a positive impact on LEG through lower BW.…”
Section: Phenotypic and Genetic Correlationsmentioning
confidence: 94%
“…Several physiological, behavioural, and production-related variables have been used to measure wellbeing and its opposite pole, stress (Barnett and Hemsworth 1990;Pedersen 1996;Korhonen et al 2001a). The data collection methods employed in behavioural investigations are based on either video recordings or visual observations.…”
Section: Introductionmentioning
confidence: 99%
“…It does not, however, measure the duration or frequency of the behaviour or the transaction times between different behaviour patterns (Altmann 1974). Numbers of different behaviours can be identified in video recordings (Hansen and Berthelsen 2000;Korhonen et al 2001a). Analysis of video recordings is therefore laborious, especially when the sampling interval is short.…”
Section: Introductionmentioning
confidence: 99%